Short Video Endorse , Program Afiliasi Melalui Trust dan Keputusan Pembelian Produk Fashion pada Platform Tiktok di Indonesia - Ramadhani, Kurniawan; In, Churin; Wijaya, Ade Taruna (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
This study aims to determine the effect of short video endorsements and affiliate programs through trust on purchasing decisions for fashion products on the Tiktok platform in Indonesia. The Tiktok platform provides many features such as videos, songs, stickers, live and others so that users can compete with models and styles, from artists to ordinary people who want to share their creativity. The busy Tiktok social media is currently used by business people in marketing their products through Tiktok content. This type of research is a quantitative research with path analysis method. The sample in this study was 132 people who had purchased fashion products on Tiktok. The results of this study indicate that short video endorsements have a significant effect on trust and purchase decisions. Affiliate program has a significant effect on trust and purchasing decisions. However, the trust variable as an intervening agent is not strong enough to mediate the short video endorse and affiliate program variables on purchasing decisions